Connect Park : um aplicativo mobile para interações no bioma Cerrado na perspectiva do ensino de ciências naturais inclusivo - Garin, Douglas Mendonça (2021)
This qualitative research aimed to investigate whether the use of mobile applications in educational practices inherent of Natural Sciences teaching can contribute to the improve the students learning. We also seek to investigate the potential of using an application for mobile device (Mobile App) involving concepts inherent to the Cerrado biome as learning objects of Natural Sciences, in the inclusive perspective, ensuring the rights of students who present some physical, sensory and/or cognitive impairment to knowledge access. In the systematic literature review, we detected only 63 studies using Mobile Apps involving these subjects, but those ones do not focus specifically on our research object. In order to discuss and reach a consensus on the importance of using digital technology used as a pedagogical tool to aid the construction of knowledge by elementary school students, we were guided by the use of active learning methods. We bring about the opinion of experts on the subject, whom were heard using the DELPHI method, which is based on a questionnaire applied to a panel of experts. The data analysis followed Bardin’s speech, who suggests the categorization of data. We listed 4 categories for our analysis: (1) discover how the mobile device application can be used as a teaching tool; (2) discuss and implement actions on school inclusion of people with physical, intellectual and sensory disabilities, (3) identify and define parameters for the investigative approach and the use of the scientific method and (4) understand how teachers see and use the active learning method. The results obtained from the research collaborators indicate the good acceptance of the proposal and suggest that the trail and the Connect Park application created by us constitute a possibility in promoting education and environmental conservation, aiming at the protection of native plant species from the cerrado biome. in the park chosen as the research locus for the inclusive field class.his process of teaching about the Cerrado biome, in an inclusive perspective. We also seek to investigate the potential of using an application for mobile device (Mobile App) involving concepts inherent to the cerrado biome as learning objects of Natural Sciences, in the inclusive perspective of students who present some physical, sensory and/or cognitive impairment. In the systematic literature review, we detected only 63 studies using Mobile Apps involving these subjects, but those that propose them do not focus on our research object. In order to discuss and reach a consensus on the importance of using digital technology used as a pedagogical tool to aid the construction of knowledge of elementary school students, we are guided by the use of active learning methods. We seek to hear the opinion of experts on the subject, during the data collection phase, using the DELPHI method, which is based on a questionnaire applied to a panel of experts. The form of data analysis follows Bardin, who suggests the categorization of data. We listed 4 categories for our analysis: (1) discover how the mobile device application can be used as a teaching tool; (2) discuss and implement actions on school inclusion of people with physical, intellectual and sensory disabilities, (3) identify and define parameters for the investigative approach and the use of the scientific method and (4) understand how teachers see and use the active learning method. The results obtained from the research collaborators indicate the good acceptance of the proposal and suggest that the trail and the Connect Park application created by us constitute a possibility in promoting education and environmental conservation, aiming at the protection of native plant species from the cerrado biome. in the park chosen as the research locus for the inclusive field class.